The Oxford handbook of the Bible and ecology - Marlow, Hilary ca. 20./21. Jh.; Harris, Mark (Oxford Handbooks Ser., 2022)
Does the Bible have anything to contribute to contemporary concerns about the environment? This collection of essays on the Bible and ecology explores biblical texts and their interpretation in the light of ecological issues. The handbook covers a number of political and ethical issues, as well as offering detailed exploration of individual Bible books. It discusses a number of controversial views, including whether the Judeo-Christian tradition has contributed to the environmental crisis, and how the Bible is used by climate change deniers.